Evidence of tool use in a seabird - Fayet, A; Hansen, E; Biro, D (National Academy of Sciences, 2019)
Documenting novel cases of tool use in wild animals can inform our understanding of the evolutionary drivers of the behavior’s emergence in the natural world. We describe a previously unknown tool-use behavior for wild birds, so far only documented in the wild in primates and elephants. We observed 2 Atlantic puffins at their breeding colonies, one in Wales and the other in Iceland (the latter captured on camera), spontaneously using a small wooden stick to scratch their bodies. The importance of these observations is 3-fold. First, while to date only a single form of body-care-related tool use has been recorded in wild birds (anting), our finding shows that the wild avian tool-use repertoire is wider than previously thought and extends to contexts other than food extraction. Second, we expand the taxonomic breadth of tool use to include another group of birds, seabirds, and a different suborder (Lari). Third, our independent observations span a distance of more than 1,700 km, suggesting that occasional tool use may be widespread in this group, and that seabirds’ physical cognition may have been underestimated.